Association of Polymyalgia Rheumatica With Socioeconomic Status in Primary Care: A Cross‐Sectional Observational Study. Issue 6 (June 2014) - Hayward, Richard A.; Rathod, Trishna; Muller, Sara; Hider, Samantha L.; Roddy, Edward; Mallen, Christian D.
<x xml:space="preserve">Abstract</x> Objective Polymyalgia rheumatica (PMR) is an inflammatory musculoskeletal condition predominantly diagnosed and managed in the community. Socioeconomic status (SES) is known to be associated with many inflammatory rheumatologic conditions, but has not been investigated in relation to PMR. This study aimed to investigate the association between PMR and SES at both the area and individual levels. Methods Patients ages >50 years registered with 8 general practices in North Staffordshire were sent a questionnaire requesting details of their general health, SES, and lifestyle. Individual SES was measured using occupation, educational level, and perceived adequacy of income. Area‐level SES was measured using the Index of Multiple Deprivation, derived from respondents' postcodes. Electronic primary care medical records were searched for Read code diagnoses of PMR 2 years before and after the survey. Results Of the 13, 831 respondents, 141 had a recorded PMR diagnosis in their electronic medical records, a prevalence of 10 per 1, 000 patients. No association between PMR and SES was seen at either the individual or area level. Conclusion No association was found between PMR and SES at either the area or individual level. Unlike several of the inflammatory arthritides that are more common in the more deprived areas, PMR shows no such association. In part this may be due to PMR affecting an older population. Although socioeconomic factors are important for clinicians and researchers to consider, in patients with PMR, further epidemiologic work is needed to fully characterize this disabling disorder.